2019
DOI: 10.1108/jpbm-08-2018-1997
|View full text |Cite
|
Sign up to set email alerts
|

Engaging consumers in mobile instant messaging: the role of cute branded emoticons

Abstract: Purpose With the rapid surge of mobile marketing, an increasing number of brands have launched branded emoticons in an attempt to build brand relationships with consumers. Despite the apparent promise of branded emoticon usage, there is only limited academic research on branded emoticons. This paper aims to build on impression management theory and the conceptualization of cuteness to investigate how the effect of cuteness in branded emoticon design influences perceived playfulness in mobile instant messaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 115 publications
(166 reference statements)
2
33
0
2
Order By: Relevance
“…In this study, the term playfulness refers to the essence of play accompanied by positive experiences using SNSs [5]. Perceived playfulness is found to influence consumers' behavioral intentions in various contexts, such as online games [31] and SNS channels [43]. Hsieh and Tseng [5] also found that using both text messages and emoticons in mobile instant messaging can increase information richness and is positively connected to a person's perceived playfulness.…”
Section: Playfulnessmentioning
confidence: 90%
See 4 more Smart Citations
“…In this study, the term playfulness refers to the essence of play accompanied by positive experiences using SNSs [5]. Perceived playfulness is found to influence consumers' behavioral intentions in various contexts, such as online games [31] and SNS channels [43]. Hsieh and Tseng [5] also found that using both text messages and emoticons in mobile instant messaging can increase information richness and is positively connected to a person's perceived playfulness.…”
Section: Playfulnessmentioning
confidence: 90%
“…Thus, purchasing emojis is a unique consumption practice for consumers who choose to show their individuality. Thus, the purchasing of emojis helps satisfy consumers' needs for uniqueness [31]. Based on the results of these studies, it is inferred that the level of need for uniqueness in an individual is closely related to the intention to purchase emojis.…”
Section: Need For Uniquenessmentioning
confidence: 97%
See 3 more Smart Citations